The Original Plan of the East End of St Hugh's Choir at Lincoln Cathedral Reconsidered in the Light of New Evidence. Issue 1 (1st January 2016) - Harrison, Stuart
Abstract : The recent identification of two original drawings of the excavated remains of the east end of St Hugh's choir at Lincoln Cathedral adds new information to that first published in 1887. A review of this information and fresh survey of the site, which includes information from grave slabs, will enlarge our understanding of what was discovered, including the fact that the foundations had been badly damaged by grave digging. The drawings themselves are revealed to be part reconstructions rather than accurate representations of what had actually survived. Nevertheless, they do allow a more accurate plan of the remains to be drafted and a new reconstruction of the building to be attempted. This is the aim of this article.